NILAI ESTETIKA PARIKAN LEBARAN PADA RUBRIK KOPI GIRAS HARIAN JAWA POS EDISI AGUSTUS SAMPAI SEPTEMBER 2012 - Al Hakim, M Idris; Astuti, Sri Budi (Buana Bastra, 2014)
Abstract Parikan is a kind of poetry that has up consists of four arrays, each array consisting of four syllables. The first and secon d array is sampiran, while the third and fourth array is the content, as well as the guru song first array with the third array and the second array is equal to the fourth array. Parikan similar to the poem in Indonesian literature. Parikan are identic with the Java language, especially the use of typical alkaline parikan Suroboyoan, has now appeared in various shows and med ia. One of the communications media of the most interesting and most widely reaching throughout society is the print media. Parikan one that appears in the print media is on the rubric Coffee parikan Giras present each year at the Jawa Pos daily. parikan that appear on the rubric is a medium for bersilahturahmi. Parikan itself usually contains advice, satire, humor, lore. In thi s study, parikan will be assessed in terms of aesthetic. By focusing on the problems of (1) the aesthetic value of the rubric C offee Giras diction in terms of accuracy, (2) the aesthetic value of the rubric Coffee Giras in terms of style. The purpose of this study was (1) to describe the aesthetic value of the rubric Coffee parikan Giras diction in terms of accuracy, (2) describe the aesthetic value of the rubric Coffee parikan Giras measured in terms of style. The data in this study in the form of aesthetic value includes the value of aesthetics in terms of precision of diction and style aesthetic value. Sources of data in this study on the rubric of parikan Jawa Pos Daily Coffee Giras August-September issue of 2012. Data collection techniques used in this study documentation. Data analysis used descriptive qualitative techniques, using qualitative descriptive technique works step is to describe an object, phenomenon terjewantah in a narrative writing. That is, data collected by the form of words rather than numbers. Large number of facts and data is stored in the form of documentation materials. Based on the analysis of data it can be concluded that the aesthetic value Parikan Lebaran on Rubric Coffee Giras Jawa Pos Daily Edition August to September 2012 to study the accuracy stilistika which includes the use of diction and style indicated the use of connotative meaning in parikan widths. Connotative meanings that exist in parikan arise as a result of social attitudes, personal attitudes and additional criteria imposed on a conceptual meaning. While the style of the language on the parikan only within the scope of rhetorical style, rhetorical style is a style that is merely a deviation from the usual construction to achieve a certain effect with use of the meaning expressed directly. Rhetorical style consists of 21 kinds of style, but the study found the use of fo rce five languages, ranging from stylistic Alliteration, assonance style, style, Asidenton, style and style Polisidenton Ellipsis. So the style that is in theory not all there in the rubric parikan Coffee Giras, while for patterns generated prosody rubric parikan on Coffee Giras varied widely used pattern and produce a beautiful sound aesthetic values heard. Then the overall aesthetic value parikan on Jawa Pos Daily is beautiful and easy to understand its contents. Key Word : Aesthetic value, parikan, diction, style